Research on the anti-perspective correction algorithm of QR barcode - Li, J.; Wang, Y.-W.; Wang, Y.; Chen, Y.; Wang, G. (Journal of Digital Information Management, 2013)
2-D (2-dimension) bar code has many advantages compared with 1-D bar code, so it has many prevalent applications in recent days. However, there're several factors that affecting the sampling process, they lead to a certain degree of deformation towards the 2-D bar code. Furthermore, this deformation may too severe for 2-D bar code to be recognized. Generally, the main stream of twisted image correcting is based on the approach of control-point transformation. So how to locate the control point accurately becomes a key factor in 2-D bar code correcting. This paper develops a QR barcode searching graph and gets the precise location of control point. Experiment shows that our algorithm has good efficiency and accuracy.
Keywords: Image correction; Line fitting; Perspective transformation; QR code; Searching graphics